Enhanced electrocatalytic ethanol oxidation reaction in alkaline media over Pt on a 2D BiVO4-modified electrode under visible light irradiation. Issue 14 (28th June 2018) - Hu, Jiayue; Zhai, Chunyang; Zeng, Lixi; Du, Yukou; Zhu, Mingshan
Abstract : 2D BiVO4 is extended to be a visible-light-responsive support for opening a new application of electrocatalytic ethanol oxidation reaction (EOR). Abstract : Bismuth vanadate (BiVO4 ), as a typical visible-light-activated semiconductor, has attracted much attention in water oxidation. In this paper, we extend it to be a visible-light responsive support for the application of electrocatalytic ethanol oxidation reaction (EOR). Firstly, two dimensional (2D) BiVO4 nanosheets were synthesized, and then worked as the support for the decoration of Pt nanoparticles. Pt nanoparticles of ultra-small size with an average diameter of 3.5 nm were well dispersed on the surface of as-synthesized 2D BiVO4 nanosheets. By using the as-prepared Pt–BiVO4 as a working electrode, 2.7 folds enhanced catalytic activity for the EOR were achieved under visible light irradiation compared to that under dark conditions. The synergistic effect of photocatalysis and electrocatalysis together with the 2D structure of BiVO4 result in the improvement of the catalytic performance.